AskTheCode: Interactive Call Graph Exploration for Error Fixing and Prevention - Husák, Robert; Kofroň, Jan; Zavoral, Filip (Electronic Communications of the EASST, 2019)
In order to prevent and fix errors in program code, developers need to understand its semantics to a significant extent. For this purpose, they use various approaches, such as manual call graph exploration or dynamic analysis with a debugger. However, these techniques tend to be cumbersome in a larger codebase, because they provide either underapproximate or overapproximate results and it is often hard to combine them. Therefore, we present AskTheCode, a Microsoft Visual Studio extension enabling to interactively explore a call graph, ensuring that only feasible execution traces are taken into consideration. AskTheCode is based on control flow analysis and backward symbolic execution. We show its potential to significantly improve developers' experience on a complex code example.